(untitled) (Research, Society and Development, 2021)
The creation of this Online Community Extension Project is based on the idea of minimizing current socio-economic and health deficiency issues, caused by the COVID-19 pandemic, while strategically complementing with existing Odontology content. In order to spread information and knowledge to the population in general, involve the academic and non-academic community on debating and disseminating the themes in the project about health and dentistry; the development of these subjects was made through videos, lives and posts on Instagram’s®️ platform. The produced content through social media enables fast sharing of information, knowledge and curiosities about oral health along with sistemic health. The obtained results show the high spread of the posts, as well as including extensionists projects, which has the possibility of being made online. After this project’s conclusion, it was possible to notice the great social media range, the positive impact that the healthcare field can cause on population through sharing knowledge and information, in order to provide better life and health quality.